Influence of zonular tension on molecular transport in the porcine ocular lens - Crews, Morgan; Rich, Wade; Reilly, Matthew A. (Frontiers in Ophthalmology, 2024)
IntroductionAccommodation is the process of changing the ocular lens’ refractive power and focal distance. This process involves application of biomechanical forces on the lens by the surrounding musculature. Previous studies have demonstrated that the lens epithelium demonstrates mechanotransduction and that tension influences its chemical activity. It is not yet known how these forces affect the structure and permeability of the lens. This study aimed to identify the influence of tension on molecular transport of dyes through the lens.MethodsPaired porcine eyes were incubated in each of four dyes for three time periods with no stretch (null), static, or cyclic stretching using a bespoke mechanical lens stretcher. After incubation, the lenses were frozen and cryosectioned sagittally through the optic axis. Photographs of the stretched and unstretched lenses were compared and qualitatively assessed.ResultsNone of the four dyes showed drastic stretch-induced differences in dye penetration depth. However, the dye neutral red showed dramatic stretch-induced changes in the dye uptake color behind lens anterior surfaces, with unstretched lenses appearing far more orange than their stretched counterparts. Three of four dyes showed notable differences between anterior and posterior diffusion patterns. One dye, methylene blue, demonstrated unexpected intensity in the lens nucleus compared to the lower intensity shown in the cortex, suggesting active transport rather than a linearly graded passive diffusion regardless of stretching condition.DiscussionAll this taken together suggests that lens transport is more complex than simple passive diffusion and that active transport of some molecules may be affected by stretching. Future work should assess the mechanisms of transport for the various dyes and attempt to explain the dye permeation patterns observed here, including the effects of stretching.